Height Accuracy of Radargrammetric Generated Digital Elevation Model - Abdul Samad, Abdul Hadi (2002)
The stereoscopic concept used in photogrammetry was successfully extended to the optical sensor of SPOT (System Probatoire d'Observation de la Terre) to generate the digital elevation model (DEM) and to extract the planimetric features. Following this success, scientists are impressively encouraged to explore the feasibility of using stereoscopy on synthetic aperture radar (SAR) images, applying the radargrammetric technique. In the regions where cloud cover or darkness prevails, active microwave remote sensing data such as SAR can be fully utilized to procure information about land surface and forest canopy. The objective of this study is to analyze the accuracy of the elevations extracted from the DEM generated using the radargrammetric technique as compared with the elevations generated from the photogrammetric technique. The capability of the radargrammetric technique and its potential in extracting the altimetric information were subsequently assessed. The stereo RADARSAT images of Klang Valley with coverage of 100 Ian by 100 Ian were acquired. A total of 199 Ground Control Points (GCPs) were selected on relatively low terrains as backscattering radar data is very sensitive to the slope and high terrains. The primary input data was the coordinates of GCPs which were extracted from the topographical maps. When the errors produced in the GCP collection report were acceptable, the next process was creating epipolar images and generating DEM. It was then followed by generating the geocoded DEM.